Modeling of Passive and Forced Convection Heat Transfer in Channels with Rib Turbulators - Jan Stąsiek (MDPI AG, 2021)
The main goal of the research presented in this paper was the experimental and numerical analysis of heat enhancement and aerodynamic phenomena during air flow in a channel equipped with flow turbulators in the form of properly configured ribs. The use of ribs intensifies the heat transfer and at the same time increases not only the flow resistance but also the energy costs. Therefore, designing modern heat exchangers with optimal thermal and flow parameters requires the knowledge of the theory of heat exchangers as well as measurement methods and numerical calculations. Bearing in mind the above, the liquid crystal techniques (LCT), particle image velocimetry (PIV) and digital image processing (DIP) for temperature, velocity, friction factor and heat transfer coefficient measurements are presented herein. These three optical tools (using desktop computers) create an extremely powerful and advanced measuring technique that has not been available anywhere before. Brief histories of these measurement methods and techniques are discussed and some examples are presented. In order to assess and select the value of the measurement technique, local and average distributions of Nusselt numbers (in the measurement section) obtained by the transit analysis method on the inter-rib regions of a plate coated by thermochromics liquid crystal and heated by air as an alternative to the steady-state analysis. In the parallel, numerical calculation was performed with the use of the ANSYS Fluent software code and supported by laser anemometry-computed turbulence intensity of air flow. Comparison of the Nusselt number distributions was determined by three methods, i.e., steady state, the transient method and CFD simulation. Up to three-fold enhancement of the local heat transfer capability was observed. Failure to take into account the surface of the ribs in heat transfer causes differences in the obtained results of the Nusselt number depending on the method used. Apart from the heat transfer data, the pressure drop in the form of friction factors is also presented. On the basis of the conducted research, it can be stated that both qualitative and quantitative coherence was obtained between the experimental and computational studies.